Cyclotron Production of High–Specific Activity Co and In Vivo Evaluation of the Stability of Co Metal-Chelate-Peptide Complexes - Tara Mastren; Bernadette V. Marquez; Deborah E. Sultan; Elizabeth Bollinger; Paul Eisenbeis; Tom Voller; Suzanne E. Lapi (Molecular Imaging)
This work describes the production of high–specific activity 55 Co and the evaluation of the stability of 55 Co-metal-chelate-peptide complexes in vivo. 55 Co was produced via the 58 Ni(p,α) 55 Co reaction and purified using anion exchange chromatography with an average recovery of 92% and an average specific activity of 1.96 GBq/μmol. 55 Co-DO3A and 55 Co-NO2A peptide complexes were radiolabeled at 3.7 MBq/μg and injected into HCT-116 tumor xenografted mice. Positron emission tomography (PET) and biodistribution studies were performed at 24 and 48 hours postinjection and compared to those of 55 CoCl 2 . Both 55 Co-metal-chelate complexes demonstrated good in vivo stability by reducing the radiotracers’ uptake in the liver by sixfold at 24 hours with ˜ 1% ID/g and at 48 hours with ˜ 0.5% ID/g and reducing uptake in the heart by fourfold at 24 hours with ˜ 0.7% ID/g and sevenfold at 48 hours with ˜ 0.35% ID/g. These results support the use of 55 Co as a promising new radiotracer for PET imaging of cancer and other diseases.